LIVING HADITH AND LOCAL WISDOM: A PHENOMENOLOGICAL STUDY OF THE ANNYORONG LOPI TRADITION IN SOUTHEAST ASIA - Mulla Shadra, Yasser; Saddriana, Saddriana; Tajuddin, Muhammad Saleh (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2025)
This study explores the intersection between Islamic teachings and local traditions within the Annyorong Lopi ritual in Bontobahari District, Bulukumba, with particular emphasis on the concept of Living Hadith—how hadith values are not merely understood as textual doctrine but are actively embodied in the community’s cultural practices. The primary aim of this study is to investigate the existence of the Annyorong Lopi ritual, describe its implementation process, analyze the forms of acculturation between Islamic principles and indigenous customs, and examine the actualization of hadith values within this tradition. The study adopts a descriptive qualitative method, guided by a religious phenomenological approach. Data were collected through participatory observation, in-depth interviews with traditional and religious leaders, including Panrita Lopi, and documentation of ritual artifacts and texts. The findings indicate that Annyorong Lopi continues to thrive as a sustainable, adaptive, and spiritually infused cultural heritage. Across each stage of the procession, from selecting an auspicious day, performing the Appassili and Ammossi rituals, to launching the boat, Islamic values such as gratitude (shukr), trust in God (tawakkal), brotherhood (ukhuwah), and reverence for ancestors are seamlessly integrated. The encounter between Islam and local tradition is characterized by complementary acculturation, wherein religious and cultural elements coexist and reinforce one another. The values of Living Hadith are reflected in communal cooperation, collective prayer, and the balance between human effort and divine reliance. This study contributes significantly to understanding how Islamic values are embedded within local cultural expressions and highlights the role such practices play in preserving cultural heritage while reinforcing the religious identity of coastal communities. Abstrak Penelitian ini mengkaji perjumpaan Islam dan tradisi lokal dalam ritual Annyorong Lopi di Kecamatan Bontobahari, Bulukumba, dengan fokus pada dimensi Living Hadis, yaitu bagaimana nilai-nilai hadis tidak hanya dipahami sebagai teks, tetapi juga dihidupkan dalam praktik budaya masyarakat. Tujuan utama penelitian ini adalah untuk mengungkap eksistensi ritual Annyorong Lopi, merinci prosesi pelaksanaannya, menjelaskan bentuk akulturasi antara ajaran Islam dan tradisi lokal, serta menelaah aktualisasi nilai-nilai hadis dalam tradisi tersebut. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan fenomenologi agama. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam dengan tokoh adat dan agama serta Panrita Lopi, dan dokumentasi artefak serta teks ritual Hasil penelitian menunjukkan bahwa Annyorong Lopi tetap eksis sebagai warisan budaya yang lestari, adaptif, dan religius. Dalam tiap tahap prosesi mulai dari penentuan hari baik, ritual Appassili, Ammossi, hingga peluncuran perahu terintegrasi nilai-nilai Islam seperti syukur, tawakkal, ukhuwah, dan penghormatan terhadap leluhur. Perjumpaan antara Islam dan tradisi berlangsung dalam bentuk akulturasi yang saling melengkapi. Nilai-nilai Living Hadis terwujud melalui gotong royong, doa bersama, serta harmoni antara ikhtiar dan tawakkal. Penelitian ini memberikan kontribusi penting dalam memahami bagaimana nilai-nilai Islam terintegrasi ke dalam praktik budaya lokal, serta bagaimana praktik tersebut berperan dalam melestarikan warisan budaya sekaligus memperkuat identitas keagamaan masyarakat pesisir.